Absence of the Caspases 1/11 Modulates Liver Global Lipid Profile and Gut Microbiota in High-Fat-Diet-Induced Obese Mice - de Sant'Ana, Lívia Pimentel; Ribeiro, Dalila Juliana S.; Martins, Aline Maria Araújo; dos Santos, Fábio Neves; Corrêa, Rafael; Almeida, Raquel das Neves; Eberlin, Marcos Nogueira; Maurice, Corinne F.; Magalhães, Kelly Grace (Frontiers in Immunology, 2020)
Obesity is a chronic disease with rising worldwide prevalence and largely associated with several other comorbidities, such as cancer, non-alcoholic fatty liver disease (NAFLD), and metabolic syndrome. Hepatic steatosis, a hallmark of NAFLD, is strongly correlated with obesity and has been correlated with changes in the gut microbiota, which can promote its development through the production of short-chain fatty acids (SCFAs) that regulate insulin resistance, bile acid, choline metabolism, and inflammation. Recent studies have suggested a controversial role for the inflammasome/caspase-1 in the development of obesity and non-alcoholic steatohepatitis (NASH). Here, we evaluated the role of inflammasome NLRP3 and caspases 1/11 in the establishment of obesity and hepatic steatosis in diet-induced obese mice, correlating them with the global lipid profile of the liver and gut microbiota diversity. After feeding wild-type, caspases 1/11, and NLRP3 knockout mice with a standard fat diet (SFD) or a high-fat diet (HFD), we found that the caspases 1/11 knockout mice, but not NLRP3 knockout mice, were more susceptible to HFD-induced obesity, and developed enhanced hepatic steatosis even under SFD conditions. Lipidomics analysis of the liver, assessed by MALDI-MS analysis, revealed that the HFD triggered a significant change in global lipid profile in the liver of WT mice compared to those fed an SFD, and this profile was modified by the lack of caspases 1/11 and NLRP3. The absence of caspases 1/11 was also correlated with an increased presence of triacylglycerol in the liver. Gut microbial diversity analysis, using 16S rRNA gene sequencing, showed that there was also an increase of Proteobacteria and a higher Firmicutes/Bacteroidetes ratio in the gut of caspases 1/11 knockout mice fed an HFD. Overall, mice without caspases 1/11 harbored gut bacterial phyla involved with weight gain, obesity, and hepatic steatosis. Taken together, our data suggest an important role for caspases 1/11 in the lipid composition of the liver and in the modulation of the gut microbial community composition. Our results further suggest that HFD-induced obesity and the absence of caspases 1/11 may regulate both lipid metabolism and gut microbial diversity, and therefore may be associated with NAFLD and obesity.